Two-year follow-up after endobronchial coil treatment in emphysema: results from the REVOLENS study. Issue 6 (21st December 2017) - Deslée, Gaëtan; Leroy, Sylvie; Perotin, Jeanne Marie; Mal, Hervé; Dutau, Hervé; Bourdin, Arnaud; Vergnon, Jean Michel; Pison, Christophe; Kessler, Romain; Jounieaux, Vincent; Salaün, Mathieu; Marceau, Armelle; et al.
Severe emphysema is a difficult to treat condition with limited efficacy of currently available treatments. Endobronchial coil treatment (ECT) is a minimally invasive endobronchial treatment which consists of placing shape-memory nitinol coils in emphysematous lobes to enhance lung recoil and reduce lung hyperinflation at rest and during exercise [1, 2]. Randomised studies demonstrated an improvement in exercise capacity, lung function and quality of life, and showed an acceptable safety profile at 1 year [3–6]. However, to our best knowledge, longer term safety and effectiveness results beyond 1 year have not been reported thus far. In severe emphysema, endobronchial coils improve quality of life with an acceptable safety profile at 2 years http://ow.ly/eVlg30gKrPE